Treatment of chicken processing wastewater using hybrid upflow anaerobic sludge blanket (HUASB) coupled with aerated lagoon (AL) - Mat Daud, Nur Falilah (2016)
Chicken processing center in Parit Raja, Johor was operated in small or medium scale and using certain equipment and machinery. Mostly, chicken processing center was located near to the drainage and their untreated wastewater discharged directly to the drainage system. The wastewater produced by chicken processing wastewater is known for its high pollutants and it will pollute the environment. Therefore, it must treated prior to discharge. One of the method to be considered is anaerobic digestion. Anaerobic wastewater treatment has been used as a main technology for the treatment of medium and high strength wastewater. In this study, upflow anaerobic sludge bed (UASB) and hybrid-UASB (HUASB) reactors were combined with aerobic treatment using aerated lagoon (AL) to treat chicken processing wastewater. Steel slag was used as filter media in the HUASB. This research aimed to investigate the efficiency of combined anerobic and aerobic treatement using HUASB-AL system. Effects of temperature and determination removal rate coefficient, k during the operation are also investigated. Through this research, three reactors had been installed namely HUASB-AL (R1), HUASB-AL (R2) and UASBAL (R3). R1 and R3 were operated at ambient temperature (26±3°C) meanwhile R2 was operated at thermophilic temperature (50±5°C). The average removals of parameters tested ranged between 90-95% for COD, 90-93% for BOD, 46-86% for total suspended solids, 29-49% for ammonia nitrogen and 82-84% for total phosphorus. Average gas productions were recorded as 4742 mL/gCOD, 5261 mL/gCOD and 4192 mL/gCOD for R1, R2 and R3 respectively. In addition, the average removal rate coefficient, k’ values were 2.0668 d-1, 2.1265 d-1 and 1.6996 d- 1 for R1, R2 and R3 respectively. All the k‘ values occurred at OLR 4.32 g COD/L.d for both R1 and R3 and 4.55 g COD/L.d. for R2. The development of sludge granulation also studied. Overall, the HUASB reactors that operated at thermophilic temperature had performed better than HUASB and UASB reactor that operated at ambient temperature. The results obtained from this study will contribute to a better understanding of chicken processing wastewater thus provide a better treatment method.